ANALISIS KINERJA PEGAWAI PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH DI KABUPATEN TAMBRAUW BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Daisiu, Sussan A; Murary, Weron; Morintoh, Raymond R (Ensiklopedia Education Review, 2024)
Abstract: Effective human resource management is directly related to the success of efforts to improve employee performance, both at the individual level, at the work group level, and at the organizational level, the Secretariat of the Tambrauw Regency Regional People's Representative Council as an institution tasked with providing services to the community either directly or indirectly, but the main task and function is to provide the best service for DPRD members,  For this reason, it is necessary for employees to have skills and professionalism that are balanced with the demands, in order to know the performance of employees at the secretariat of the Tambrauw Regency Regional House of Representatives Based on Law Number 23 of 2014 and the factors that cause Employee Performance at the Secretariat of the Tambrauw Regency Regional House of Representatives to be not optimal. The research used by the author is part of normative law and empirical law research. Primary data is data obtained directly from the field based on respondents and sources, secondary data, data collection in this literature study is carried out by studying and collecting data related to the object of research. The analysis of this study takes place together with the data collection process, or is carried out after the data is collected. The results of the research obtained by the DPRD secretariat are tasked with providing administrative, technical, and operational support to the DPRD in carrying out legislation, budget, and supervisory functions. This includes coaching employees at the DPRD Secretariat to ensure they have the necessary skills and knowledge, employees at the DPRD Secretariat must understand their authority and responsibilities in accordance with the applicable laws and regulations, capacity building of local government apparatus through training and development, this includes employees at the DPRD Secretariat who need to continue to improve their competencies to support the tasks of the District DPRD Tambrauw. Employees who are not disciplined tend not to comply with work rules and schedules, which ultimately reduces productivity, an unconducive work environment, such as inadequate facilities or less harmonious relationships between employees, can also affect employee performance.Keywords: Tambrauw Regency, Performance, DPRD Secretariat